A method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings and its product
By adding steel slag and rubidium tailings into ceramic materials, using Rb-K-Na-Ca-Mg-Fe multi-system and in-situ crystal phase generation method, the problems of limited strength improvement and resource waste are solved, and the low-temperature preparation of high-strength ceramic blanks are achieved and the effect of energy saving and consumption reduction is achieved.
Patent Information
- Application Number
- CN202311584603.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-11-26
- Publication Date
- 2025-04-01
- Estimated Expiration
- 2043-11-26
AI Technical Summary
The strength improvement of existing ceramic materials is limited, cost is high and cannot be produced on a large scale, and the utilization rate of steel slag and rubidium tailings is low, resulting in waste of resources and environmental pollution.
By incorporating steel slag and rubidium tailings, using Rb-K-Na-Ca-Mg-Fe multi-system, the raw material ratio and formula system are optimized, and high-strength ceramic blanks are prepared at low temperatures, and the in-situ crystal phase is used to increase the strength of the ceramic material.
It greatly reduces the firing temperature of ceramic products, improves the flexural strength of ceramic materials, reduces energy consumption and environmental pollution, and realizes lightweighting and energy saving and consumption reduction of ceramic materials.
Smart Images

Figure CN117550876B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ceramic materials, and in particular to a method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings, and a product thereof. Background Art
[0002] As a large ceramic production country, China has a relatively mature industrial line while also consuming a large amount of resources. With the continuous depletion of ceramic raw materials and energy, the ceramic industry urgently needs to establish an innovation-driven energy-saving and consumption-reducing green ceramic production model by increasing revenue and reducing expenditure. This includes two aspects: one is to utilize mining waste rocks abandoned in the industrial production process, solid waste residues after combustion, unqualified raw material tailings, and waste generated in the smelting or chemical production process; the other is to reduce the firing temperature without affecting the performance of ceramic products, so as to reduce the loss of kiln tools and save fuel, thereby improving productivity and reducing production costs.
[0003] Steel slag is a solid byproduct produced during the smelting process of the steel industry, with an annual output of 10-15% of crude steel production. The current annual crude steel production in China exceeds 800 million tons, but the utilization rate of steel slag is only 30%; rubidium tailings are solid waste produced in mineral processing operations. Under the current technical and economic conditions, it is not suitable for further sorting and has a low recycling value. The stacking of steel slag and rubidium tailings not only requires a large amount of land, but also easily causes environmental pollution such as air and water bodies. Therefore, the reuse of steel slag and rubidium tailings needs to be given corresponding attention. Using steel slag and rubidium tailings as raw materials for ceramic production is not only conducive to alleviating the unfavorable situation of polluting the environment and occupying land, but also can replace existing high-priced raw materials, further reducing the cost of raw materials, and can optimize the formulation system to increase the strength of ceramic products while reducing their firing temperature, in order to obtain greater economic benefits.
[0004] At present, the main ways to improve the strength of ceramic materials include eliminating defects, refining grains, increasing the density of ceramic body sintering, introducing reinforcing phases, and prestressing. However, these methods can only improve the flexural strength of ceramic materials to a certain extent, and there are still a series of problems such as limited improvement, high cost, and inability to mass produce. Summary of the invention
[0005] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings. By adding solid waste and low value-added minerals, optimizing the raw material ratio and formula system, and using the Rb-K-Na-Ca-Mg-Fe multi-element system, the firing temperature of ceramic products is greatly reduced and the firing temperature range is widened. By generating a crystalline phase in situ, the strength of the ceramic material is effectively improved, thereby achieving the purpose of reducing energy consumption and green environmental protection. Another purpose of the present invention is to provide a product prepared by the above-mentioned preparation method.
[0006] The purpose of the present invention is achieved through the following technical solutions:
[0007] The present invention provides a method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings. The raw materials of the ceramic body are composed of 18-25wt% of kaolin, 8-10wt% of quartz sand, 15-20wt% of silty shale, 11-15wt% of steel slag, 6-9wt% of potassium feldspar, 8-10wt% of wollastonite, 8-11wt% of burned talc and 10-15wt% of rubidium tailings. The preparation method comprises the following steps:
[0008] (1) The raw materials are weighed according to the ratio, and then wet ball milled to obtain a slurry, which is then dried, ground, and sieved to obtain a particle size distribution D 50 3.8~6.9μm, D 90 Powdered materials with a size of 7.5 to 19.1 μm;
[0009] (2) After the powder material is pressed and formed, the temperature is increased from room temperature to 1080-1120° C. at a heating rate of 10-20° C. / min, and the temperature is kept at that temperature for 30-90 min. After the temperature is kept at that temperature, the powder material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding steel slag and rubidium tailings.
[0010] Furthermore, the particle size of each component of the raw material of the present invention is 60-100 mesh. The time of wet ball milling in step (1) is 30-120 minutes. The pressure of pressing in step (2) is 10-12 MPa, and the pressing time is 25-35 seconds.
[0011] Furthermore, the chemical composition of the steel slag of the present invention is SiO29.32-16.35wt%, Al2O31.45-3.21wt%, K2O 0.01-0.44wt%, Na2O 0.01-0.38wt%, MgO 4.38-8.62wt%, CaO37.57-43.56wt%, Fe2O312.20-27.75wt%, TiO20.01-0.84wt%, and loss on ignition 0.50-14.50wt%; the chemical composition of the rubidium tailings is SiO245.38-57.64wt%, Al2O310.39-22.14wt%, K2O 0.84-3.12wt%, Na2O0.85-2.94wt%, MgO 0.71~2.83wt%, CaO 0.67~2.48wt%, Fe2O32.14~7.68wt%, TiO20.01~1.09wt%, Rb2O 0.35~1.14wt%, ignition loss 0.02~12.65wt%.
[0012] The product is prepared by the method of preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings. The crystal phase composition and content of the ceramic body are 38.5-43.3% of calcium feldspar, 7.7-11.3% of iron-containing diopside, and 6.5-7.7% of quartz; the flexural strength of the ceramic body is 90.8-110.3MPa, the water absorption rate is 0.04-0.38%, and the volume density is 2.47-2.49g / cm 3 , the open porosity is 0.48~0.84%.
[0013] The present invention has the following beneficial effects:
[0014] (1) A low eutectic compound is formed at high temperature by steel slag containing CaO, MgO, and Fe2O3, potassium feldspar containing K2O and Na2O, wollastonite containing CaO, calcined talc containing MgO, and rubidium tailings containing Rb2O, thereby playing a composite fluxing effect of Rb-K-Na-Ca-Mg-Fe multi-component system, greatly reducing the firing temperature of the ceramic body; the introduction of Rb2O not only plays a better fluxing role, but also widens the firing temperature range of the formula system, reduces the breakage rate and deformation rate of ceramic products during the firing process, and improves the product qualification rate.
[0015] (2) The formulation system of the present invention does not use substances that decompose and produce gas at high temperatures, which is more conducive to low-temperature sintering. By introducing Ca and Mg components through steel slag, wollastonite and calcined talc, and combining the fluxing effect of the Rb-K-Na-Ca-Mg-Fe multi-composite flux, a liquid phase can be generated at a lower temperature, so that calcium feldspar and diopside crystals have more sufficient time to nucleate and grow, thereby increasing the content of the crystalline phase in the blank and the aspect ratio of the crystal. The in-situ generated calcium feldspar and diopside crystal phases will deflect and branch the microcracks generated when the ceramic material breaks to increase the strength, and cooperate with the particle toughening effect of the residual quartz crystal phase in the blank to greatly improve the strength of the ceramic product. In addition, because steel slag introduces a large amount of Fe2O3 into the formulation system, Fe 3+ During the liquid phase sintering stage, Ca, Mg and other ions in the diopside structure are replaced, causing the diopside crystal phase to gradually transform and form columnar crystals with a higher aspect ratio and larger volume, which is also beneficial to improving the mechanical strength of the porcelain body.
[0016] (3) The present invention has a simple operation process, low cost and is easy to control. By optimizing the raw material ratio and formulation system, the firing temperature of ceramic products is greatly reduced and the firing temperature range is widened. The in-situ generation of crystal phases is adopted to effectively improve the strength of ceramic materials, which is beneficial to thinning the thickness of ceramic materials and achieving the actual requirements of energy conservation and consumption reduction. At the same time, it also provides an effective solution to the ownership and reuse of solid wastes such as steel slag and rubidium tailings, and low-value-added minerals such as siltstone, which is of great significance in reducing energy consumption and green environmental protection. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] The present invention will be further described in detail below in conjunction with the embodiments and drawings:
[0018] Figure 1 is a scanning electron microscope image of a ceramic body prepared in an embodiment of the present invention;
[0019] Figure 2 The figure is the XRD spectrum of the ceramic body prepared in the embodiment of the present invention. DETAILED DESCRIPTION
[0020] Embodiment 1:
[0021] The present embodiment provides a method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings. The raw materials of the ceramic body are 25wt% kaolin, 10wt% quartz sand, 20wt% silty shale, 11wt% steel slag, 6wt% potassium feldspar, 9wt% wollastonite, 9wt% calcined talc, and 10wt% rubidium tailings. The particle size of each raw material component is 60-100 meshes. The preparation method has the following steps:
[0022] (1) The above raw materials were weighed according to the ratio, and then wet-milled for 30 min at a ratio of material: ball: water = 1:2:1 to obtain a slurry. The obtained slurry was dried at 100°C for 6 h, ground, and passed through a 100-mesh standard sieve to obtain a particle size distribution D 50 6.9μm, D 90 Powdered material of 19.1μm;
[0023] (2) The powdered material is pressed into shape at a pressure of 10 MPa for 25 seconds; after the pressing, the temperature is increased from room temperature to 1080°C at a heating rate of 15°C / min for sintering, and the temperature is kept for 90 minutes. After the temperature is kept, the powdered material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding steel slag and rubidium tailings.
[0024] Embodiment 2:
[0025] The present embodiment provides a method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings. The raw materials of the ceramic body are 24wt% kaolin, 9wt% quartz sand, 18wt% silty shale, 13wt% steel slag, 7wt% potassium feldspar, 8wt% wollastonite, 9wt% calcined talc, and 12wt% rubidium tailings. The particle size of each raw material component is 60-100 meshes. The preparation method has the following steps:
[0026] (1) The above raw materials were weighed according to the ratio, and then wet-milled for 60 min at a ratio of material: ball: water = 1:2:1 to obtain a slurry. The obtained slurry was dried at 100°C for 6 h, ground, and passed through a 120-mesh standard sieve to obtain a particle size distribution D 50 5.4μm, D 90 Powdered materials with a diameter of 15.6 μm;
[0027] (2) The powdered material is pressed into shape at a pressure of 10 MPa for 30 seconds; after the pressing, the temperature is increased from room temperature to 1100°C at a heating rate of 20°C / min for sintering, and the temperature is kept for 60 minutes. After the temperature is kept, the powdered material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding steel slag and rubidium tailings.
[0028] Embodiment three:
[0029] The present embodiment provides a method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings. The raw materials of the ceramic body are 18wt% kaolin, 10wt% quartz sand, 15wt% silty shale, 15wt% steel slag, 7wt% potassium feldspar, 10wt% wollastonite, 11wt% burned talc, and 14wt% rubidium tailings. The particle size of each raw material component is 60-100 meshes. The preparation method has the following steps:
[0030] (1) The above raw materials were weighed according to the ratio, and then wet-milled for 90 min at a ratio of material: ball: water = 1:2:1 to obtain a slurry. The obtained slurry was dried at 100°C for 6 h, ground, and passed through a 150-mesh standard sieve to obtain a particle size distribution D 50 4.2μm, D 90 Powdered materials with a diameter of 10.3 μm;
[0031] (2) The powdered material is pressed into shape at a pressure of 12 MPa for 30 seconds; after the pressing, the temperature is raised from room temperature to 1110°C at a heating rate of 15°C / min for sintering, and the temperature is kept for 30 minutes. After the temperature is kept, the powdered material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding steel slag and rubidium tailings.
[0032] Embodiment 4:
[0033] The present embodiment provides a method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings. The raw materials of the ceramic body are 20wt% kaolin, 8wt% quartz sand, 17wt% silty shale, 15wt% steel slag, 9wt% potassium feldspar, 8wt% wollastonite, 8wt% calcined talc, and 15wt% rubidium tailings. The particle size of each raw material component is 60-100 meshes. The preparation method has the following steps:
[0034] (1) The above raw materials were weighed according to the ratio, and then wet-milled for 120 min at a ratio of material: ball: water = 1:2:1 to obtain a slurry. The obtained slurry was dried at 100°C for 6 h, ground, and passed through a 180-mesh standard sieve to obtain a particle size distribution D 50 3.8μm, D 90 Powdered materials with a diameter of 7.5 μm;
[0035] (2) The powdered material is pressed into shape at a pressure of 12 MPa for 35 seconds; after the pressing, the temperature is raised from room temperature to 1120°C at a heating rate of 20°C / min for sintering, and the temperature is kept for 60 minutes. After the temperature is kept, the powdered material is naturally cooled to room temperature in the furnace to obtain a high-strength ceramic body prepared at low temperature by adding steel slag and rubidium tailings.
[0036] The chemical composition of the raw materials of the ceramic green body of the embodiment of the present invention is shown in Table 1.
[0037] Table 1 Chemical composition of ceramic raw materials of the present invention (wt%)
[0038]
[0039] The ceramic body prepared in the embodiment of the present invention has a crystal phase composition of calcium feldspar, iron-containing diopside, and quartz (see Figure 2 );like Figure 1As shown, the morphology of iron-containing diopside is columnar, with a length of 10 to 30 μm and an aspect ratio of 6 to 10:1.
[0040] The ceramic green body without adding steel slag and rubidium tailings is used as a comparative example (other conditions are the same as those of Example 1). The performance tests of the ceramic green bodies prepared in the examples of the present invention and the comparative examples are shown in Table 2.
[0041] Table 2 Performance indicators of ceramic bodies of the embodiments of the present invention and comparative examples
[0042]
[0043] The results in Table 2 show that the ceramic body of the comparative example without adding the steel slag and rubidium tailings system has a low sintering degree and has problems such as high porosity, high water absorption, low bulk density and low flexural strength. The embodiment of the present invention can not only achieve low-temperature sintering under the steel slag and rubidium tailings system, but also has performance indicators far higher than the flexural strength ≥35MPa and water absorption ≤0.5% specified in the national standard GB / T 4100-2015, which is also significantly better than the comparative example, achieving the actual requirements of lightweight ceramic materials and energy saving and consumption reduction.
Claims
1. A method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings, characterized in that: The raw material composition of the ceramic body is kaolin 18-25wt%, quartz sand 8-10wt%, silty shale 15-20wt%, steel slag 11-15wt%, potassium feldspar 6-9wt%, wollastonite 8-10wt%, calcined talc 8-11wt%, rubidium tailings 10-15wt%; the chemical composition of the steel slag is SiO2 9.32-16.35wt%, Al2O3 1.45-3.21wt%, K2O 0.01-0.44wt%, Na2O 0.01-0.38wt%, MgO 4.38-8.62wt%, CaO 37.57-43.56wt%, Fe2O312.20-27.75wt%, TiO20.01-0.84wt%, loss on ignition 0.50-14.50wt%; the chemical composition of the rubidium tailings is SiO245.38-57.64wt%, Al2O310.39-22.14wt%, K2O 0.84-3.12wt%, Na2O 0.85-2.94wt%, MgO 0.71-2.83wt%, CaO 0.67-2.48wt%, Fe2O32.14-7.68wt%, TiO20.01-1.09wt%, Rb2O 0.35-1.14wt%, loss on ignition 0.02-12.65wt%; the particle size of each component of the raw materials is 60-100 mesh; the preparation method comprises the following steps: (1) The raw materials are weighed according to the ratio, and then wet ball milled to obtain a slurry, which is then dried, ground, and sieved to obtain a particle size distribution D 50 3.8~6.9μm, D 90 Powdered materials with a size of 7.5 to 19.1 μm; (2) After the powder material is pressed and formed, the temperature is raised from room temperature to 1080-1120° C. at a heating rate of 10-20° C. / min, and the temperature is kept for 30-90 minutes. After the temperature is kept, the powder material is naturally cooled to room temperature with the furnace, thereby obtaining a high-strength ceramic body prepared at low temperature by adding steel slag and rubidium tailings; the crystal phase composition and mass percentage content of the ceramic body are 38.5-43.3% of anorthite, 7.7-11.3% of iron-containing diopside, and 6.5-7.7% of quartz; the iron-containing diopside The morphology is columnar, with a length of 10 to 30 μm and an aspect ratio of 6 to 10:
1. The in-situ generated calcium feldspar and diopside crystal phases can deflect and bifurcate the microcracks generated when the ceramic material breaks to increase the strength, and cooperate with the particle toughening effect of the residual quartz crystal phase in the green body to greatly improve the strength of the ceramic product. The flexural strength of the ceramic green body is 90.8 to 110.3 MPa, the water absorption rate is 0.04 to 0.38%, and the volume density is 2.47 to 2.49 g / cm 3 , the open porosity is 0.48~0.84%.
2. The method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings according to claim 1, characterized in that: The time of wet ball milling in step (1) is 30 to 120 minutes.
3. The method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings according to claim 1, characterized in that: The pressure of the pressing process in step (2) is 10-12 MPa, and the pressing time is 25-35 s.
4. A product obtained by the method for preparing a high-strength ceramic body at low temperature by adding steel slag and rubidium tailings as described in any one of claims 1 to 3.
Citation Information
Patent Citations
Low-temperature fired high-strength building ceramic green body and preparation method thereof
CN114349492A
Preparation method for firing high-strength building ceramic green body at low temperature by adopting low-cost raw materials and product of high-strength building ceramic green body
CN115536359A